Fabrication of homogenous three‐dimensional biomimetic tissue for mass spectrometry imaging. (11th April 2019) - Song, Xiaowei; He, Jiuming; Li, Chao; Sun, Chenglong; Pang, Xuechao; Zhang, Jin; Zang, Qingce; Luo, Zhigang; Li, Xin; Zhang, Ruiping; Abliz, Zeper
Abstract: Reference samples are essential for mass spectrometric method optimization, data quality control, and target analyte quantitation. However, it is highly challenging to prepare an ideal homogeneous, standard‐spiked tissue sample for mass spectrometry imaging (MSI) research. Herein, we present a standard‐spiked 3D biomimetic tissue model fabricated with native cells, homogenate matrix, and biocompatible polymer. Unlike traditional homogenized tissue surrogates or those constructed with "on‐tissue" or "under‐tissue" micropipetting strategies, this simulated tissue shares both structural integrity of cells and homogeneous properties of matrix. As a result, analyte standards could undergo more in‐depth incorporation and has a more comparable native status with a real tissue. Series of tissue sections made from the 3D tissue model were proven to be feasible and useful for the parameter optimization, analyte quantitation, and calibration curve fitting for the air‐flow assisted desorption electrospray ionization MSI. Additionally, by analyzing the quality control model sections, we proposed a median principal component score calibration and demonstrated that this method can normalize instrumental fluctuations to stable levels in a large‐scale untargeted MSI experiments for the reliable metabolomic biomarker discovery. Thus, these results indicated that the standard‐spiked 3D biomimetic tissue has convincing significance in MSI analysis